2022
DOI: 10.1038/s41598-022-21051-4
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopes of C and N differ in their ability to reconstruct diets of cattle fed C3–C4 forage diets

Abstract: Stable isotopes are useful for estimating livestock diet selection. The objective was to compare δ13C and δ15N to estimate diet proportion of C3–C4 forages when steers (Bos spp.) were fed quantities of rhizoma peanut (Arachisglabrata; RP; C3) and bahiagrass (Paspalumnotatum; C4).Treatments were proportions of RP with bahiagrass hay: 100% bahiagrass (0%RP); 25% RP + 75% bahiagrass (25%RP); 50% RP + 50% bahiagrass (50%RP); 75% RP + 25% bahiagrass (75%RP); and 100% RP (100% RP). Feces, plasma, red blood cell (RBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Overall, our results are consistent with previous studies that have found a significant relationship between the isotopic information in hair and feces (Crumsey et al 2019), reflecting isotopic patterns of diet sources. Moreover, our results corroborate with a recent study conducted by Jaramillo et al (2022) on using δ 13 C and δ 15 N in feces, hair, blood, and plasma samples to predict diet composition of cattle fed mixed C 3 -C 4 forages. They concluded that fecal δ 13 C was the best predictor to accurately reconstruct cattle diets.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Overall, our results are consistent with previous studies that have found a significant relationship between the isotopic information in hair and feces (Crumsey et al 2019), reflecting isotopic patterns of diet sources. Moreover, our results corroborate with a recent study conducted by Jaramillo et al (2022) on using δ 13 C and δ 15 N in feces, hair, blood, and plasma samples to predict diet composition of cattle fed mixed C 3 -C 4 forages. They concluded that fecal δ 13 C was the best predictor to accurately reconstruct cattle diets.…”
Section: Discussionsupporting
confidence: 91%
“…As mentioned by Gannes et al (1997) , the 15 N/ 14 N ratio in animal tissue increases as animals are nutritionally stressed. Previous studies stated that 15 N enrichment is a response to a negative energy balance (caused by nutrient deficit) that leads to body mass loss from recycling of muscle tissue causing enrichment of 15 N ( Rysava et al 2016 ;Crumsey et al 2019 ;Funck et al 2020 ;Jaramillo et al 2022 ). Body mass loss due to forage deficit is an issue during potential feed gaps, especially in the arid warm zone on livestock-only farms ( Lamega et al 2021 ).…”
Section: Determining Seasonal Dynamics Of Feed Supplymentioning
confidence: 99%
See 3 more Smart Citations